2022
DOI: 10.1136/archdischild-2021-322483
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of fosfomycin in neonatal sepsis: pharmacokinetics and safety in relation to sodium overload

Abstract: ObjectiveTo assess pharmacokinetics and changes to sodium levels in addition to adverse events (AEs) associated with fosfomycin among neonates with clinical sepsis.DesignA single-centre open-label randomised controlled trial.SettingKilifi County Hospital, Kenya.Patients120 neonates aged ≤28 days admitted being treated with standard-of-care (SOC) antibiotics for sepsis: ampicillin and gentamicin between March 2018 and February 2019.InterventionWe randomly assigned half the participants to receive additional int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 39 publications
(73 reference statements)
0
18
0
Order By: Relevance
“…Notably, 34.4% of isolates belonging to S. Stanleyville, S. Menston and S. Haelsingborg were shown to contain fosfomycin resistance genes, however we did not test for phenotypic resistance against this drug. Fosfomycin is a broad spectrum antimicrobial that is often used as drug of last resort in the treatment of chronic bacterial infections in human and is presently being promoted as a treatment of choice for life-threatening sepsis in African settings ( Falagas et al, 2016 ; Kane et al, 2021 ; Obiero et al, 2022 ). Detection of fosfomycin resistance in day-old chicks is worrisome, because it indicates possible administration of this antimicrobial to day-old chicks or grandparent stock.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, 34.4% of isolates belonging to S. Stanleyville, S. Menston and S. Haelsingborg were shown to contain fosfomycin resistance genes, however we did not test for phenotypic resistance against this drug. Fosfomycin is a broad spectrum antimicrobial that is often used as drug of last resort in the treatment of chronic bacterial infections in human and is presently being promoted as a treatment of choice for life-threatening sepsis in African settings ( Falagas et al, 2016 ; Kane et al, 2021 ; Obiero et al, 2022 ). Detection of fosfomycin resistance in day-old chicks is worrisome, because it indicates possible administration of this antimicrobial to day-old chicks or grandparent stock.…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference in rate of adverse events between SOC-F and SOC, 2.2 events/100 infant-days and 3.2 events/100 infant days (95% TRAN exposure and rate of adverse events in combination with SOC regimen (ampicillin plus gentamicin). 25 Additionally, four 23,29,30,33 of the six studies with reported outcomes for UTI were observational in nature and the remaining two 31,32 randomized controlled studies examined fosfomycin as a single dose for lower UTI. Although more research is needed to further define the optimal PD target, as well as PK, safety and outcomes for repeated oral and IV dosing in infants and children, fosfomycin tromethamine offers an important option for pediatric patients, particularly for treatment of MDR UTI in the United States.…”
Section: Clinic Al S Tudie Smentioning
confidence: 99%
“…21,22 The first PK and clinical experience of fosfomycin tromethamine in children reported a mean peak serum concentration (C max ) and area under concentration-time curve (AUC) ranged from 11.3 to 25.3 mcg/mL and 53.7 to 139 mcg × h/mL, respectively, following a single dose of 19tients with neonatal sepsis 24,25. The reported mean gestational age (GA), post-natal age (PNA), and weight was 39.8 weeks, 2.7 days, and 2.872 kg, respectively.…”
mentioning
confidence: 99%
“…Fosfomycin has a negligible PPB rate and change in plasma protein concentration is not an important factor here [ 172 ]. Other antibiotics with very low PPB rates include aminoglycosides, so change in PPB is not expected in neonates [ 20 ].…”
Section: General Considerations On Neonate’s Pharmacokineticsmentioning
confidence: 99%